A Study of New Separation Axioms in Topology Induced by \(θ\)-sgp-Open Sets - Page, Md. Hanif; Hosamath, V. T.; Patil, Anuradha N. (Communications in Mathematics and Applications, 2021)
This paper introduces separation axioms using \(θ\)-sgp-open sets in topological spaces. We also focus on some of their basic properties and also made the implication of these axioms among themselves and with other known axioms. Also we investigated characterizations of these axioms. It also introduces the concept of sober \(θ\)-sgp-\(R_0\) spaces.